Synthesis of low coercive BaFe12O19 hexaferrite for microwave applications in low-temperature cofired ceramic - Rane, Vivek A.; Meena, Sher Singh; Gokhale, Suresh P.; Yusuf, S. M.; Phatak, Girish J.; Date, Sadgopal K. (Journal of Electronic Materials, 2013)
Polycrystalline M-type barium hexaferrite (BaFe12O19) samples have been synthesized by solution combustion route at different pH and calcination conditions in order to reduce the coercivity for microwave applications in low-temperature cofired ceramic (LTCC) substrates. Structural, morphological, and magnetic properties of BaFe12O19 were studied by x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Raman spectroscopy, vibrating sample magnetometry (VSM), and Mossbauer spectroscopy. The formation of a single-phase hexagonal structure was confirmed by XRD. The Raman spectra reveal all characteristic peaks of BaFe12O19, illustrating the phase purity and crystal lattice symmetry of the synthesized material. Mossbauer spectra illustrate the existence of Fe3+ cations at all five crystallographic lattice sites. The microstructural features observed by FESEM disclose the growth of nanoregime particles into hexagonal platelet particles after calcination at temperatures from 800A degrees C to 1200A degrees C. The VSM results show a lower coercivity (1350 Oe to 3500 Oe) together with reasonably high saturation magnetization (55 emu/g to 60 emu/g) and a high bulk resistivity (> 10(9) Omega-cm) at room temperature. The dependence of magnetic and electrical properties on the preparation and processing conditions is also discussed.
Keywords: Barium hexaferrite; coercivity; LTCC; Mossbauer spectroscopy; Raman spectroscopy

Structural, electrochemical and catalytic activity of Prussian blue analogues embedded with functionalized carbon for solid state battery applications - Shaikh, Shabana P. S.; Bhatt, Pramod; Yusuf, S. M.; Bhange, S. N.; Bansod, Sudhakar; Abdalla, Abdalla M. (International Journal of Hydrogen Energy, 2020)
The nanoparticles of Mn-1.5[Cr(CN)(6)]center dot mH(2)O@Ni-1.5[Cr(CN)(6)]center dot nH(2)O core-shell prussian blue analogues (PBA) embedded with carbon additives (PBA-C) were synthesized and characterized as electrode material for solid state battery application. The impedance spectroscopy and cyclic voltametry were used to study the electrochemical properties by adding functionalized carbon in 1:1 proportion to improve the electrical performance. The value of room temperature electrical conductivity of core-shell PBA and core-shell nanoparticles mixed with vulcan carbon (PBA-C) are found to be 1.574 x 10(-3) and 1.92 x 10(-3) Scm(-1), respectively. Using Li2La3Zr2O12 (LZZO) electrolyte, single cell was fabricated with PBA-C material, and studied its charging-discharging cycles, which exhibits higher current density with stable performance for 400 cycles for time slots of 400 min. The study reveals that the PBA core-shell nanoparticles mixed with carbon (PBA-C) may be a potential candidate as an electrode material in the form of a single cell using LZZO electrolyte. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: cyclic voltametry; Electrolyte; Prussian blue analogues (PBA); Solid state battery; XPS